Das dritte und vierte Relief von Gundük - Aguilar, Juan; Miglus, Peter A. (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2019)
The Gundük rock relief ensemble in a cave located in the northern highlands of Iraq is probably the oldest known example of its kind in the Near East. First reported in the 19th century but never accurately documented, unfortunately two of the three known reliefs were intentionally damaged beyond repair in the decades to follow. This article presents a new art-historical analysis of the preserved third relief as well as a fourth previously unknown carving, based on recent photogrammetric capture. The images can be dated to the Early Dynastic III or Early Akkadian period with motifs, stylistic details and a composition obviously deriving from then-contemporaneous art in southern Mesopotamia.